This distracted and anarchical people new answers for old questions about the Civil War-era North - Slap, Andrew L.; Smith, Michael Thomas 1970-. (New York Fordham University Press, 2013)
The essays in this book range widely throughout the history of the Civil War North, using new methods and sources to re-examine old theories and discover new aspects of America's greatest conflict. Many of these issues are just as important today as they were a century and a half ago.
Includes bibliographical references and index.
Keywords: Electronic books; United States -- History -- Civil War, 1861-1865.; United States -- Politics and government -- 1861-1865.